The Relationship of Organizational Justice with Organizational Commitment, Organizational Trust, and Job Satisfaction of Employees of Sistan and Baluchestan Education Office - Abdol Ali Keshtegar (Journal of Global Pharma Technology, 2018)
Organizational justice refers to employee's feeling and understanding about fairness and equity in work behaviors and relationships. Various researches show that the increase of justice affects different aspects of organizational behavior. Based on this, current research tries to examine how the aspects of organizational justice and dimensions of its subset (including distributional, procedural, and relational justice) affect job satisfaction, organizational commitment, and organizational trust. Statistical population of current research is 120 employees of schools of Sistan and Baluchestan education organization. Standard questionnaires were distributed randomly among 40 statistical samples by using Cochrane formula. Niehoff and Moorman questionnaire was used for measuring aspects of organizational justice, Minnesota's questionnaire (MSQ) for job satisfaction was used for measuring job satisfaction of employee, Meyer, Allen, and Smith questionnaire was used for measuring organizational commitment, and Ellonen et al questionnaire (ot) was used for measuring organizational trust. Data analysis with SPSS software showed that the distribution of data is normal and therefore, Pearson correlation test was used for determining the relationship of variables. Results showed that all hypotheses of research are supported and there is a positive and significant relationship between organizational justice and job satisfaction, organizational commitment, and organizational trustKeywords: Organizational justice, Job satisfaction, Organizational commitment, Education organization, Sistan and Baluchestan.